Ion-Pairs in Aluminosilicate-Alkali Synthesis Liquids Determine the Aluminum Content and Topology of Crystallizing Zeolites - Asselman, Karel; Pellens, Nick; Thijs, Barbara; Doppelhammer, Nikolaus; Haouas, Mohamed; Taulelle, Francis; Martens, Johan A; Breynaert, Eric; Kirschhock, Christine E A (Chemistry of materials, 2022)
Using hydrated silicate ionic liquids, phase selection and framework silicon-to-aluminum ratio during inorganic zeolite synthesis were studied as a function of batch composition. Consisting of homogeneous single phasic liquids, this synthesis concept allows careful control of crystallization parameters and evaluation of yield and sample homogeneity. Ternary phase diagrams were constructed for syntheses at 90 °C for 1 week. The results reveal a cation-dependent continuous relation between batch stoichiometry and framework aluminum content, valid across the phase boundaries of all different zeolites formed in the system. The framework aluminum content directly correlates to the type of alkali cation and gradually changes with batch alkalinity and dilution. This suggests that the observed zeolites form through a solution-mediated mechanism involving the concerted assembly of soluble cation-oligomer ion pairs. Phase selection is a consequence of the stability for a particular framework at the given aluminum content and alkali type.